Multispectroscopic and Molecular Docking Insight into Elucidating the Interaction of Irisin with Rivastigmine Tartrate: A Combinational Therapy Approach to Fight Alzheimer’s Disease - Waseem, Rashid (ACS Omega, 2021)
[Image: see text] This study was aimed to study the interaction between purified irisin and rivastigmine tartrate (RT), a cholinesterase inhibitor used in Alzheimer’s therapy. Irisin mainly promotes brown fat-like features in white adipose tissues; however, it has some important role in the nervous system also, i.e., capable of opposing synapse and memory failure in Alzheimer’s disease (AD). The recombinant protein was purified by Ni–NTA chromatography and characterized using spectroscopic and in silico techniques. Further, the mechanism of interaction between irisin and RT was investigated using various biophysical techniques. Fluorescence quenching studies suggested that there exists a moderate binding between irisin and RT with a binding constant (K) of 10(4) M(–1) and the irisin–RT complex is guided by a combination of both static and dynamic modes of quenching. Thermodynamic parameters suggested the reaction to be driven by hydrogen bonding, making it specific. FTIR and CD spectroscopy suggested no secondary structural alterations in irisin in the presence of RT. Molecular docking investigation provided an insight into the important residues that play a key role in irisin–RT interactions. This study delineates an important finding in AD therapy and can provide a platform further to explore the potential of irisin in AD treatment.